Comprehensive utilization of waste residue from lithium extraction process of spodumene. (15th August 2021) - Wang, Xu; Hu, Haisheng; Liu, Meitang; Li, Yunfei; Tang, Yong; Zhuang, Lun; Tian, Benjun
Highlights: High value products were successfully synthesized from waste residue. Lithium slag is fully utilized and no waste is produced. The whole process meets the requirements of environmental protection. Abstract: In this work, the comprehensive utilization of spodumene waste residue - lithium slag is achieved. An experimental scheme of hydrothermal preparation of nano-kaolinite and xonotlite from it is proposed. The W-lithium slag is completely decomposed into sodalite and then transformed into hydroxycancrinite in 6 mol/kg NaOH solution at 220 ℃. As an intermediate product, hydroxycancrinite was reacted with 0.65 mol/kg HNO3 solution at 260 ℃ for 24 h to prepare nano-kaolinite successfully. The desiliconization filtrate produced by the reaction of W-lithium slag and NaOH solution was used as raw material, mixed with CaO and reacted at 260 ℃ for 12 h after aging for 12 h, then xonotlite was successfully prepared. This work demonstrates great potential on green recycling of spodumene waste residue from lithium extraction process and introduce a new economical processing technique for the slag as well.